Sensibilidade de fungos deteriorantes de produtos de panificação à conservantes - Moro, Camila Brombilla (2019)
Currently, economic losses due to the disposal of fungal-spoiled foods are large, and the use of organic acids as a preservative in food represents a control alternative to this problem. The objective of this work was to evaluate the influence of acetic, sorbic and propionic acids on the growth of fungal species in culture media, under different pH conditions. The genera Penicillium, Aspergillus and Hyphopichia isolated from bakery products and a Penicillium roqueforti strain (IMI 217568) originally isolated from Stilton cheese were accessed. To evaluate their sensitivity to organic acids commonly employed in bakeries for fungal control, 12 isolates were cultivated in culture medium with four pH levels (4.5, 5.0, 5.5 and 6.0) and three organic acids: acetic acid (0; 25 ; 50; 100; 200; 400 and 800 mM), sorbic acid (0; 1; 2; 4; 8; 16 and 32 mM) and propionic acid (0, 1, 2, 4, 8, 16, 32, 64 , 128, 256, 512 and 1,024 mM). The experiments were conducted in duplicate and incubated for seven days to determine the minimum inhibitory concentrations (MIC). Differences were observed in the sensitivity of the species tested to the acids evaluated. The genus Aspergillus was the most sensitive when confronted with acetic acid; Hyphopichia was the more sensitive when submitted to sorbic acid; and for propionic acid, Aspergillus and Hyphopichia behaved similarly. The genus Penicillium was the most resistant in relation to the other fungi tested when exposed to these acids. In addition, a difference was observed in the inhibitory concentration of the cheese-derived Penicillium roqueforti strain when compared to the other three fungal strains isolated from spoiled bakery products. This cheese strain, had sensitivity similar to the one observed in Penicillium paneum strains. It was also observed a direct relationship between pH values and inhibitory concentration. In general, each pH increase of 0.5, doubled the acid concentrations necessary to inhibit the growth of a fungal isolate. These results demonstrated the importance of considering the pH and fungal species inducing losses in bakery products of industries when deciding the dosage of organic acids to be applied in order to ensure the increase the product stability against fungal deterioration.